Computed tomography phenotyping of perivascular adipose tissue for cardiovascular disease diagnosis and risk stratification - Oikonomou, EK (2020)
Coronary inflammation is a major driver of cardiovascular disease and has been implicated in all stages of coronary atherosclerosis, from the early formation of coronary lesions to plaque rupture. Far from being an innocent bystander, perivascular adipose tissue (PVAT) is now recognised as a critical regulator of vascular biology. Further to its direct effects on the arterial wall through outside-to-inside paracrine signals mediated by a wide range of adipocytokines, recent evidence suggests that PVAT may also function as a sensor of vascular biology. More specifically, we have shown that coronary inflammation inhibits adipogenesis and triggers lipolysis in the adjacent perivascular adipocytes, resulting in smaller, fat-free adipocytes closer to the diseased artery. These phenotypic changes can now be captured as perivascular attenuation (radiodensity) gradients on coronary computed tomography angiography (CCTA) using a novel metric, the perivascular Fat Attenuation Index (FAI).